2013
DOI: 10.1007/s12010-013-0655-7
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of a Milk-clotting Protease Produced in Submerged Fermentation by the Thermophilic Fungus Thermomucor indicae-seudaticae N31

Abstract: Proteases are some of the most important industrial enzymes, and one of their main applications is for the production of cheese in the dairy industry. Due to a shortage of animal rennet, microbial coagulant proteases are being sought. In this work, the production of microbial rennet from Thermomucor indicae-seudaticae N31 was studied in submerged fermentation. The best enzyme production was obtained in a fermentation medium containing 4 % wheat bran as the substrate in 0.3 % saline solution, incubated for 72 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 31 publications
2
15
1
Order By: Relevance
“…Peptidases from thermophilic fungi have been evaluated in relation to their biochemical properties (e.g. thermal stability) and industrial applications, for instance, Thermoascus aurantiacus and its hydrolytic activity on bovine casein [ 10 ], Thermomucor indicae-seudatiacea and Rhizomucor miehei in milk clotting activity [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Peptidases from thermophilic fungi have been evaluated in relation to their biochemical properties (e.g. thermal stability) and industrial applications, for instance, Thermoascus aurantiacus and its hydrolytic activity on bovine casein [ 10 ], Thermomucor indicae-seudatiacea and Rhizomucor miehei in milk clotting activity [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…(), Silva et al . () and Tubesha and Al‐Delaimy () have observed 40, 72 and 96 h as the optimal incubation period for MCE production by Nocardiopsis sp., Thermomucorindicae‐seudaticae and Mucor J20, respectively. On the other hand, P. oxalicum required even longer static incubation of 8 days (Hashem ).…”
Section: Resultsmentioning
confidence: 93%
“…between pH 4.0 and 4.5 for 24 h (Silva et al . ) and from B. subtilis K‐26, it was most stable at pH 7.5 (Rao and Mathur 1979). Some neutral and alkali proteases have also been isolated from Bacillus amyloliquefaciens FSE‐68 which were 100% stable for 60 min at 30C in the alkali range (Cho et al .…”
Section: Resultsmentioning
confidence: 99%
“…The values of milkclotting activity and coagulant ratio were significative to P. albidus (73.39 U/ml and 21.60, respectively). Silva et al (2014) reported milk-clotting activity ( 60.5 U/ml) and coagulant ratio (510) in Thermomucor indicae-seudaticae N31. In the study of Alecrim et al (2015), Aspergillus flavo furcatis DPUA 1493 presented milk-clotting activity of 68.61 U/ml and coagulant ratio of 1.81.…”
Section: Resultsmentioning
confidence: 99%